Descortesía, agresión y violencia verbal en tres sitios de noticias en Facebook. Opiniones en torno al discurso discriminatorio - Sepúlveda Legorreta, Norma Patricia (Comparative Cultural Studies: European and Latin American Perspectives, 2019)
Among the most important characteristics in the study of the opposite pole of politeness is, according to Blas Arroyo (2010), the observation that both the character and degree of impoliteness behavior in interpersonal relationships are closely related to the contexts in which they operate, whether they are individual, cultural or institutional. The aim of this paper is to analyze impoliteness in virtual contexts with special reference to aggressive, violent and discriminatory discourse that appears in three news sites on Facebook. For the analysis of the impoliteness we have selected a corpus constituted by a total of 225 opinions that appear in Aristegui Noticias, Animal Político and Sin Embargo MX, with reference to the discriminatory expressions of three public officials towards indigenous people in Mexico in 2014, 2015 and 2016. We start here with the distinction between the concepts of impoliteness, aggressiveness and verbal violence exposed in Fuentes and Alcaide (2008). For these authors, the relationship of impoliteness with aggressiveness and verbal violence lies in the type of strategies used to carry it out, since, in reality, many of these impoliteness strategies can be considered as aggressive and even as violent. The results obtained allow us to conclude that aggressiveness, discrimination and verbal violence are actively manifested in the selected virtual context and damage the image of the protagonists of the news, of the indigenous people and also of other users.